Initial education, curriculum, learning and teaching of writing. (Revista Investigación & praxis en CS Sociales, 2024)
This literature review was conducted to explore the available literature on the teaching of writing in early childhood education. This analysis identified the goals of early childhood education, considerations for learning and teaching writing, and curriculum construction. The purpose was to construct a state of the art for a research in development. The method was to conduct a systematic search of academic databases using Boolean equations combined with keywords from the UNESCO Thesaurus. This strategy facilitated the selection, analysis and systematization of units of analysis related to the central theme and related topics. Finally, updated information was obtained at the national and international levels, providing a broad view of initial education in relation to the processes of learning and teaching handwriting. The review highlights the relevance of quality early education, underlining the importance of effective methodologies and a well-structured curriculum to foster writing skills in children from an early age.
Keywords: education; early childhood; written language; handwriting